Nurtured and sorrowful: Positive and negative emotional appeals in early COVID-19 themed brand communications - Mensa, Marta (2023)
This study examines the prevalence of emotional appeals in COVID-19-themed brand advertisements from around the world in the months immediately following the World Health Organization’s declaration of the coronavirus outbreak as a pandemic. The study analyses the frequencies of use of positive and negative emotional appeals in the content of the ads, and concurrent combinations of such appeals. A content analysis was conducted on a sample of 376 ads from the “Ads of The World” digital archive. The results reveal a preference for positive emotions, with nurturance and affiliation being the most frequent. Sorrow was the third most preferred emotional appeal, and the most used negative emotion. Some brands have compared the virus to a hurricane (Brazil), an assassin with a chainsaw (US) or the death personified (Peru). Advertisers should be careful when using negative emotional appeal content during COVID-19. According to the law of apparent reality, during times of stress the recommendation is to be cautious with negative emotions, as they may be felt more intensely by consumers. Advertising has a social responsibility, which can be directed at promoting consumer behaviours that leave a positive or negative impact on their communities. In a situation such as the pandemic, brand communication professionals must use emotions rigorously, employing this resource to contribute to society, avoiding giving rise to harmful attitudes or behaviours. The research findings are consistent with the literature and lead to future examination of emotional appeals in advertising in stressful and uncertain circumstances.